Traveling Wave of Three-Species Stochastic Lotka-Volterra Competitive System (Journal of Nonlinear Modeling and Analysis, 2024)
This paper is devoted to a three-species stochastic competitivesystem with multiplicative noise. The existence of stochastic traveling wavesolution can be obtained by constructing sup/sub-solution and using randomdynamical system theory. Furthermore, under a more restrict assumptionon the coefficients and by applying Feynman-Kac formula, the upper/lowerbounds of asymptotic wave speed can be achieved.
Keywords: Stochastic competitive system; white noise; traveling wave solution; asymptotic wave speed.